Mental health and psychological wellbeing in the early stages of doctoral study: a systematic review. Issue 3 (3rd July 2022) - Jackman, Patricia C.; Jacobs, Lisa; Hawkins, Rebecca M.; Sisson, Kelly
ABSTRACT: As concerns about poor mental health and psychological wellbeing (wellbeing) in doctoral students grow, the early stage of doctoral study could be a prime opportunity for early intervention and prevention strategies. To inform the development of such strategies, it is important and timely to understand what is known about doctoral student mental health and wellbeing in the early stages. The aim of this systematic mixed studies review was to synthesise published research on mental health and wellbeing in early-stage doctoral students (ESDS). After conducting electronic searches on 10 databases and manual searches, 26 studies matching the eligibility criteria were identified. Thematic synthesis revealed there is limited evidence regarding the prevalence of mental health and wellbeing concerns and the effects of the transition to doctoral study on mental health and wellbeing. More promisingly, the synthesis generated understanding of factors related to mental health and wellbeing in ESDS. Finally, a single mental health and/or wellbeing intervention in ESDS was identified. The review underscores the need for more high-quality research to allow more robust conclusions to be drawn about mental health and wellbeing in ESDS.